In Vitro Release Kinetic Study of Ciprofloxacin HCl from Methocel K15M CR, Methocel K4M CR and Methocel K4M Premium Matrix Tablets (Stamford Journal of Pharmaceutical Sciences, 2010)
In the present study Ciprofloxacin HCl sustained release matrix tablet was prepared by utilizing different grades of hydroxypropyl methylcellulose (HPMC) polymers such as Methocel K4M CR, Methocel K4M Premium & Methocel K15M CR by direct compression method. Different amount of Methocel K15M CR was used to develop matrix builder in the three proposed formulations (F1-F3) for the study of release rate retardant effect at 5%, 6%, and 7% of total weight of tablet matrix respectively. The dissolution study of Methocel K15M CR based tablet matrices of those proposed formulations were carried out in the simulated gastric medium (pH 1.3) for 8 hours using USP dissolution apparatus II. Similarly Methocel K4M premium was used to develop matrix builder in another three proposed formulations (F4-F6). It was found that formulations F-4 (15%), F-5 (17%) and F-6 (18.3%) met the desired release rate of Ciprofloxacin HCl for 8hrs period. The release kinetics of formulation F-4, F-5 and F-6 followed Higuchi kinetic order. Again Methocel K4M premium was used for another three proposed formulations (F7-F9). It was found that formulations F-7 (6.7%), F-8 (12.3%) and F-9 (15.6%) met the desired release rate of Ciprofloxacin HCl for 8hrs period. The release kinetics of formulation F-7, F-8 and F-9 followed Higuchi kinetic order. Among these three polymers, Methocel K4M Premium showed better release retardant effect than Methocel K4M CR and Methocel K15M CR. Key Words: Ciprofloxacin HCl; Direct compression; Controlled release; Methocel K15M CR; Methocel K4M CR; Methocel K4M premium.DOI: 10.3329/sjps.v2i1.5814Stamford Journal of Pharmaceutical Sciences Vol.2(1) 2009: 37-43